Acute Myeloid Leukemia Cells Functionally Compromise Hematopoietic Stem/Progenitor Cells Inhibiting Normal Hematopoiesis Through the Release of Extracellular Vesicles - Trino, Stefania; Laurenzana, Ilaria; Lamorte, Daniela; Calice, Giovanni; De Stradis, Angelo; Santodirocco, Michele; Sgambato, Alessandro; Caivano, Antonella; De Luca, Luciana (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is an aggressive and heterogeneous clonal disorder of hematopoietic stem/progenitor cells (HSPCs). It is not well known how leukemia cells alter hematopoiesis promoting tumor growth and leukemic niche formation. In this study, we investigated how AML deregulates the hematopoietic process of HSPCs through the release of extracellular vesicles (EVs). First, we found that AML cells released a heterogeneous population of EVs containing microRNAs involved in AML pathogenesis. Notably, AML-EVs were able to influence the fate of HSPCs modifying their transcriptome. In fact, gene expression profile of AML-EV-treated HSPCs identified 923 down- and 630 up-regulated genes involved in hematopoiesis/differentiation, inflammatory cytokine production and cell movement. Indeed, most of the down-regulated genes are targeted by AML-EV-derived miRNAs. Furthermore, we demonstrated that AML-EVs were able to affect HSPC phenotype, modifying several biological functions, such as inhibiting cell differentiation and clonogenicity, activating inflammatory cytokine production and compromising cell movement. Indeed, a redistribution of HSPC populations was observed in AML-EV treated cells with a significant increase in the frequency of common myeloid progenitors and a reduction in granulocyte-macrophage progenitors and megakaryocyte-erythroid progenitors. This effect was accompanied by a reduction in HSPC colony formation. AML-EV treatment of HSPCs increased the levels of CCL3, IL-1B and CSF2 cytokines, involved in the inflammatory process and in cell movement, and decreased CXCR4 expression associated with a reduction of SDF-1 mediated-migration. In conclusion, this study demonstrates the existence of a powerful communication between AML cells and HSPCs, mediated by EVs, which suppresses normal hematopoiesis and potentially contributes to create a leukemic niche favorable to neoplastic development.